2019
DOI: 10.1038/s41598-019-46183-y
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and metabonomics analysis of fatty liver haemorrhagic syndrome in laying hens induced by a high-energy low-protein diet

Abstract: Fatty liver haemorrhagic syndrome (FLHS) is a widespread metabolic disease in laying hens that causes a decrease in egg production and even death. Insulin resistance is a major contributor to the pathogenesis of nonalcoholic fatty liver disease. However, the relationship between FLHS and the insulin resistance mechanisms underlying FLHS is not well elucidated. Therefore, we established an FLHS model induced by feeding a high-energy low-protein diet. In the current study, we found that the fasting glucose and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 60 publications
4
42
0
Order By: Relevance
“…In the present study, after fed 40 d of HFD, blood glucose tolerance, insulin sensitivity, and insulin concentration were decreased in hens, but these changes were alleviated by OCN administration. Similar to our results, Zhuang et al. (2019) reported that FLHS hens have higher blood glucose than the control hens detected by both OGTT and ITT.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, after fed 40 d of HFD, blood glucose tolerance, insulin sensitivity, and insulin concentration were decreased in hens, but these changes were alleviated by OCN administration. Similar to our results, Zhuang et al. (2019) reported that FLHS hens have higher blood glucose than the control hens detected by both OGTT and ITT.…”
Section: Discussionsupporting
confidence: 92%
“…Insulin is the only hyperglycemic hormone released by the pancreatic β cells in humans and various animals including chickens. Insulin resistance plays a key role in both human NAFLD and hen FLHS ( Gariani et al., 2013 ; Zhuang et al., 2019 ). In the present study, after fed 40 d of HFD, blood glucose tolerance, insulin sensitivity, and insulin concentration were decreased in hens, but these changes were alleviated by OCN administration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Related studies have shown that mannose can be used as a potential biomarker of insulin resistance ( Ferrannini et al, 2020 ). Our previous studies have also indicated that insulin resistance is highly correlated with the occurrence of FLHS in laying hens ( Zhuang et al, 2019 ). Regrettably, the results of this study showed that mannose levels decreased in the disease group at the two time points.…”
Section: Discussionmentioning
confidence: 83%